"Depressive pseudodementia" or "Melancholic dementia": a 19th century view. Issue 5 (May 1985) - Berrios, G E
Abstract : Nineteenth century views on the interaction between dementia, depressive illness, general paralysis and brain localisation are discussed in the context of a book by A Mairet entitled: Melancholic Dementia. It is shown that by 1883 there was already awareness of the fact that severe affective disorder could lead to cognitive impairment. General paralysis was the commonest diagnosis put forward to account for patients with depression who went on to develop dementia. Patients so diagnosed, however, often recovered and clinical and statistical analysis of Mairet's case histories suggests that some were in fact suffering from depressive pseudodementia. Evidence is marshalled to show that during the 19th century there was wide disagreement concerning the clinical domain, course and even histopathology of general paralysis. This casts doubt on the traditional view that this condition served as "a paradigm" for other psychiatric diseases during this period. It is shown that by the turn of the century these difficulties led to a redefinition of the concept of dementia and to a marked narrowing of the clinical bounds of general paralysis.